Factor Analysis of Food Intake and Family Care with the Nutritional Status of Toddlers in Rw 004 Kaliabang Tengah North Bekasi in 2022 - Dwita Zulaeha; Titin Eka Sugiatini (STIKep PPNI Jawa Barat, 2023)
Aims: The success of health development can be seen from the nutritional status of a community. Toddlers are a very vulnerable group with nutritional problems and require special attention because of the bad consequences that can be caused if they experience malnutrition. The age range from 0 to 3 years is the golden period in children's growth and development. In this age range, the growth of brain cells takes place faster than other periods. For this reason, children need a safe and loving environment as well as nutritional intake and stimulation from parents or caregivers. Methods : This research is quantitative analytic in nature with a cross sectional approach. The population in this study were all mothers who had toddlers aged 0-59 months, totaling 126 people, with a total sample of 35 people and the sampling technique used simple random sampling. Results : Obtained from 35 respondents as much as 71.4% (25 toddlers) with good nutritional status, 20% (7 toddlers) with underweight and as much as 8.6% (3 toddlers) with wasting. Bivariate analysis with the chi square test obtained results, from 71.4% (25 toddlers) with standard food intake showed good nutritional status and those who did not get food intake according to standards experienced underweight as much as 20% (7 toddlers) and wasting as much as 8.6% (3 toddlers). And as much as 51.4% (18 toddlers) with good parenting style showed good nutritional status compared to 28.6% (10 toddlers) with underweight details of 20% (7 toddlers) and wasting 8.6% (3 toddlers). Conclusions : the nutritional status of toddlers in RW 004 Kaliabang Tengah, North Bekasi is influenced by food intake and parenting provided by the family for toddlers with a P Value of 0.000.